Photobiomodulation Improves Serum Cytokine Response in Mild to Moderate COVID-19: The First Randomized, Double-Blind, Placebo Controlled, Pilot Study - Marashian, Seyed Mehran; Hashemian, Mohammadreza; Pourabdollah, Mihan; Nasseri, Mansour; Mahmoudian, Saeed; Reinhart, Florian; Eslaminejad, Alireza (Frontiers in Immunology, 2022)
Background: Because the major event in COVID -19 is the release of pre- and inflammatory cytokines, finding a reliable therapeutic strategy to inhibit this release, help patients manage organ damage and avoid ICU admission or severe disease progression is of paramount importance. Photobiomodulation (PBM), based on numerous studies, may help in this regard, and the present study sought to evaluate the effects of said technology on cytokine reduction. Methods: This study was conducted in the 2nd half of 2021. The current study included 52 mild-to-moderately ill COVID-19, hospitalized patients. They were divided in two groups: a Placebo group and a PBM group, treated with PBM (620-635 nm light via 8 LEDs that provide an energy density of 45.40 J/cm2 and a power density of 0.12 W/cm2), twice daily for three days, along with classical approved treatment. 28 patients were in Placebo group and 24 in PBM group. In both groups, blood samples were taken four times in three days and serum IL-6, IL-8, IL-10, and TNF-α levels were determined. Results: During the study period, in PBM group, there was a significant decrease in serum levels of IL-6 (-82.5% +/- 4, P<0.001), IL-8 (-54.4% ± 8, P<0.001), and TNF-α (-82.4% ± 8, P<0.001), although we did not detect a significant change in IL-10 during the study. The IL-6/IL-10 Ratio also improved in PBM group. The Placebo group showed no decrease or even an increase in these parameters. There were no reported complications or sequelae due to PBM therapy throughout the study. Conclusion: The major cytokines in COVID-19 pathophysiology, including IL-6, IL-8, and TNF-α, responded positively to PBM therapy and opened a new window for inhibiting and managing a cytokine storm within only 3-10 days.